Brain abscess in Srinagarind Hospital - Tangdumrongkul, Siriphong; Thanapaisal, Chaiwit; Chamadol, Wichan (Srinagarind Medical Journal, 2013)
The retrospective study of 56 cases of brain abscess receiving surgical intervention at Srinagarind Hospital during January 1985 to July 1988 was performed. The common presenting symptoms are headache (82%), history of fever (67%), nausea/vomitting (51%), deterioration of consciousness (39%) and seizure (20%). The common physical signs be detected are meningeal sign (45%), fever (temp > 37.8 c = 39%), hemiparesis (32%) and papilledema (34%). Leukocytosis (WBC > 10,000) was found in 62%. The common sources are mastoiditis (38%) and hematogenous spread (22%). Surgical intervention was performed by tapping or total excision or tapping and follow by total excision. Mortality rate is 20%.